A high-performance isolated SEPIC converter for non-electrolytic LED lighting - Ahmad S.; Tan N.M.L.; Baharuddin M.Z.; Buticchi G. (Institute of Electrical and Electronics Engineers Inc., 2023)
Efficiency; Electrolytic capacitors; High frequency transformers; Power converters; Dissipative snubbers; Higher efficiency; Inductor; Isolated single-ended primary inductor converter; Light-emitting diode driver; Lightemitting diode; Non-dissipative snubber; Non-electrolytic capacitor; Single-ended; Snubber; Light emitting diodes